Role of monocyte recruitment in hemangiosarcoma metastasis in dogs. (25th October 2016) - Regan, D. P.; Escaffi, A.; Coy, J.; Kurihara, J.; Dow, S. W.
Abstract: Canine hemangiosarcoma (HSA) is a highly malignant tumour associated with short survival times because of early and widespread metastasis. In humans and rodents, monocytes play key roles in promoting tumour metastasis through stimulating tumour cell extravasation, seeding, growth and angiogenesis. Therefore, we investigated the potential association between monocyte infiltration and tumour metastasis in HSA and other common canine tumours. Immunohistochemistry was used to quantify CD18 + monocytes within metastases. We found that HSA metastases had significantly greater numbers of CD18 + monocytes compared with metastases from other tumour types. HSA cells were the highest producers of the monocyte chemokine CCL2, and stimulated canine monocyte migration in a CCL2 dependent manner. These results are consistent with the hypothesis that overexpression of CCL2 and recruitment of large numbers of monocytes may explain in part the aggressive metastatic nature of canine HSA. Thus, therapies designed to block monocyte recruitment may be an effective adjuvant strategy for suppressing HSA metastasis in dogs.